Who should be a parent? Parenthood and the significance of reproductive choice - Junga Kim, Claire (Acta Bioethica, 2017)
The various reproductive technologies have expanded the power people have to control their bodily function. Because these technologies have brought new configurations of people whose role is central to the reproductive process, ambiguities about the attribution of parenthood have emerged. I insist that the intentional account among four explanatory frameworks for parenthood gains more validity, as opportunities to exert intention increase. I extend the intentional account, using Scanlon’s explanation of the “Value of Choice.” In the Value of Choice, Scanlon explains that choice has a justificatory power; that is, by the fact of having choice, one accepts the normative consequences of one’s decision. The current changes in reproduction technologies mean that there are several conditions to choose. While maintaining justificatory power from the Value of Choice, the intentional account becomes inclusive enough to encompass the status quo, plausible even in situations where intention does not exist or is not exerted.